Experimental Investigation On The Flow Structure Of A Hybrid Turbine Blade For Hydrokinetic Application - Bakar, Nurul Asyikin Abu (Universiti Sains Malaysia, 2021)
The hydrokinetic turbine has emerged as an alternative method for rural communities to generate energy for daily needs and to improve their living conditions. Due to the current pandemic, daily energy requirements in education are increasing, shifting from face-to-face learning to an online platform. This study aims to fabricate a hybrid turbine and analyze the flow behavior around the turbine that affects the power performance for the hydrokinetic application at various incoming flow speeds, V∞. The proposed hybrid turbine was designed by combining the two vertical axis turbines; Savonius and Darrieus turbines to overcome their respective disadvantages, as the Savonius turbine has a low power performance, while the Darrieus turbine has a low self-starting speed. The performance of the hybrid turbine is evaluated by analyzing the flow behavior around it, as well as the data on the coefficients of torque and power with respect to the tip speed ratio value. The hybrid turbine was tested in a closed-circuit wind tunnel at various flow speeds, V∞=4, 5, 6, and 7 m/s, to represent the typical river speed in Malaysia with Reynolds numbers of 89500, 112000, 134000, and 157000. The results showed that at the highest Reynolds number of 157000 the hybrid turbine has a strong flow attachment, resulting in the smallest wake size. At a higher Reynolds number, the flow separation is also delayed, resulting in a smaller recirculation region behind the turbine. The hybrid turbine shows an increase in power coefficient at the highest Reynold number of 157000 with 0.17 at a tip speed ratio of 0.66. Based on this, the hybrid turbine has the potential to be implemented for hydrokinetic applications and contribute to higher rates of electrification in Malaysia’s rural communities, particularly in Sabah and Sarawak.